Interpreting experimental fracture toughness results of quasi-brittle natural materials through multi-parameter approaches - Andrea Spagnoli; Andrea Carpinteri; Sabrina Vantadori (Fracture and Structural Integrity)
Natural stones like marbles are often employed as façade panels to externally cover buildings. These natural materials tend to exhibit a quasi-brittle nonlinear fracture behaviour which, conversely to concrete counterpart, has much less been studied in the literature. In the present paper, an experimental campaign on the so-called red Verona marble is carried out, and the results are discussed together with some previously published results on the white Carrara marble. The analysis of the two marbles as a whole allows us to discuss size effect and to point out the need for additional parameters in order to describe their fracture behaviour. The study focuses on a two-parameter model which accounts for a characteristic material length. A quantitative correlation between material microstructure features, obtained from thin sections technique, and the characteristic material length is proposed.